2012
DOI: 10.1155/2012/458712
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Liposomes within pH Responsive Microspheres for Oral Colonic Drug Delivery

Abstract: A novel liposome-in-microsphere (LIM) formulation has been created comprising drug-loaded liposomes within pH responsive Eudragit S100 microspheres. The liposomes contained the model drug 5-ASA and were coated with chitosan in order to protect them during encapsulation within the microspheres and to improve site-specific release characteristics. In vitro drug release studies showed that LIMs prevented drug release within simulated stomach and small intestine conditions with subsequent drug release occurring in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…For example, nanoparticles can be administered directly, as shown for formulations such as poly (lactic-co-glycolic acid) nanoparticles and polyacrylic acid nanoparticles to treat colitis or hypercalcemia [ 40 , 41 ]. Alternatively, nanoparticles could be loaded into capsules [ 42 , 43 ] or a pH-responsive polymer matrix for targeting to specific sections of the intestinal tract [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, nanoparticles can be administered directly, as shown for formulations such as poly (lactic-co-glycolic acid) nanoparticles and polyacrylic acid nanoparticles to treat colitis or hypercalcemia [ 40 , 41 ]. Alternatively, nanoparticles could be loaded into capsules [ 42 , 43 ] or a pH-responsive polymer matrix for targeting to specific sections of the intestinal tract [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Incorporation of CHO‐PDMAEMA into the bacterial lipid mixture produced stabilized liposomes with a pH‐sensitive functionality for stimuli‐responsive drug delivery. A liposome‐in‐microsphere (LIM) system, wherein liposomes were surrounded by a shell of Eudragit S100, a methacrylic acid copolymer, showed a pH‐dependent content release profile for potential oral colonic drug delivery . In vivo studies showed that conditions present within the large intestine (> pH 7.0) promoted the degradation of the Eudragit S100 films, thus triggering the collapse of the microspheres and release of over 85% of the encapsulated agents (5‐ASAs that are coated with chitosan), compared with <10% release from simulated stomach and small intestine conditions (pH 6.3).…”
Section: Ph‐responsive Liposomesmentioning
confidence: 99%
“…demonstrated that liposomes coated with Eudragit® have superior mucoadhesion characteristics in freshly extracted pig intestinal tissue, compared to other commonly investigated polymer coatings such as chitosan and carbopol(106). The results suggest that Eudragit® coatings may enable pH-dependent release and possibly reduce formulation clearance to enhance colon targeted drug delivery.Eudragit®-coated nano-delivery systems have demonstrated favourable pH-dependent release characteristics in vitro(107,108). For example,Barea et al (2010) reported a significant reduction in drug release from Eudragit®-coated liposomes in solutions designed to simulate the pH conditions of the stomach and small intestine(109).…”
mentioning
confidence: 99%